Unified three-port topology integrating a renewable and an energy storage system with the grid-interface operating as active power filter - Rodrigues, Ana Maria Cunha (2020)
This paper presents the experimental validation of a unified three-port topology, integrating a renewable energy source (RES) and an energy storage system (ESS) (or an electric vehicle) with the grid-interface operating as active power filter (APF). The proposed topology is based on a three-phase grid-interface (whose role is to operate as a APF grid-tied inverter capable of compensating current harmonics, imbalanced currents and low power factor), on a RES-interface for solar photovoltaic (PV) panels (whose role is to extract the maximum power from the PV panels), and on an ESS-interface for batteries (whose role is to store/inject energy according to the power management of the electrical installation). The paper presents the control algorithms for each interface within the scope of the different operation modes allowed by the unified three-port topology. Simulation and experimental results are presented in order to validate the distinguishing aspects of the proposed unified three-port topology.